2006
DOI: 10.1152/ajpcell.00258.2005
|View full text |Cite
|
Sign up to set email alerts
|

SNAT4 isoform of system A amino acid transporter is expressed in human placenta

Abstract: . SNAT4 isoform of system A amino acid transporter is expressed in human placenta. Am J Physiol Cell Physiol 290: C305-C312, 2006. First published September 7, 2005 doi:10.1152/ajpcell.00258.2005.-The system A amino acid transporter is encoded by three members of the Slc38 gene family, giving rise to three subtypes: Na ϩ -coupled neutral amino acid transporter (SNAT)1, SNAT2, and SNAT4. SNAT2 is expressed ubiquitously in mammalian tissues; SNAT1 is predominantly expressed in heart, brain, and placenta; and SNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
80
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(87 citation statements)
references
References 50 publications
7
80
0
Order By: Relevance
“…System A and system y + L are expressed at high levels in the placenta in the late stage of gestation. These results tend to be consistent with the previous studies [26,34,35]. Moreover, it has been reported that system A plays a key role in glutamine transport from the maternal side into placental cells [18,33].…”
Section: Discussionsupporting
confidence: 93%
“…System A and system y + L are expressed at high levels in the placenta in the late stage of gestation. These results tend to be consistent with the previous studies [26,34,35]. Moreover, it has been reported that system A plays a key role in glutamine transport from the maternal side into placental cells [18,33].…”
Section: Discussionsupporting
confidence: 93%
“…On the contrary, S-TGCs lining the maternal sinusoids seem to be increased in number in the TFAP2C mutant labyrinth. Deregulated levels of SLC38A4, a neutral amino acid transporter in the placenta, have been associated with abnormal fetal birth weight in humans (Desforges et al, 2006;Li et al, 2012). Fig.…”
Section: Discussionmentioning
confidence: 98%
“…SNAT4 (ATA3, SCL38A3) was identified primarily by sequence similarity. It is expressed primarily in liver and skeletal muscle (Sugawara et al 2000b) and has recently been shown to be present in the syncytiotrophoblast of the placenta (Desforges et al 2005). It is not expressed in trophoblast cell lines such as BeWo (Desforges et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It is expressed primarily in liver and skeletal muscle (Sugawara et al 2000b) and has recently been shown to be present in the syncytiotrophoblast of the placenta (Desforges et al 2005). It is not expressed in trophoblast cell lines such as BeWo (Desforges et al 2005). Whether it is primarily involved in transport of substrates for system A is not clear, since it may also transport branched-chain amino acids (Sugawara et al 2000b).…”
Section: Introductionmentioning
confidence: 99%